2021
DOI: 10.1056/nejmoa2035916
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of a Typhoid Conjugate Vaccine in Malawian Children

Abstract: Background Typhoid fever caused by multidrug-resistant H58 Salmonella Typhi is an increasing public-health threat in sub-Saharan Africa. We present phase 3 efficacy data from an African trial of a Vi-polysaccharide typhoid conjugate vaccine (Vi-TCV). Methods Children aged 9 months to 12 years in Blantyre, Malawi were randomized (1:1) in a double-blind trial to receive Vi-TCV (single dose) or group-A meningococcal control vaccine (MenA).The pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(104 citation statements)
references
References 35 publications
(35 reference statements)
3
92
0
Order By: Relevance
“…In Africa, recent results of a phase three, double blind Vi-TT efficacy trial conducted in Malawi among children nine months to 12 years showed 80.7% protection (95% CI 64.2-89.6) in intention to treat and 83.7% (95% CI 68.1-91.6) in per protocol analysis. 27 This study is important as it confirms the efficacy of mass vaccination for TF when used under real field and programmatic conditions in the African context as part of an outbreak response.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In Africa, recent results of a phase three, double blind Vi-TT efficacy trial conducted in Malawi among children nine months to 12 years showed 80.7% protection (95% CI 64.2-89.6) in intention to treat and 83.7% (95% CI 68.1-91.6) in per protocol analysis. 27 This study is important as it confirms the efficacy of mass vaccination for TF when used under real field and programmatic conditions in the African context as part of an outbreak response.…”
Section: Discussionsupporting
confidence: 52%
“…In Africa, recent results of a phase three, double blind Vi-TT efficacy trial conducted in Malawi among children nine months to 12 years showed 80.7% protection (95% CI 64.2–89.6) in intention to treat and 83.7% (95% CI 68.1–91.6) in per protocol analysis. 27…”
Section: Discussionmentioning
confidence: 99%
“…When the analysis was restricted to the WHO clinical diagnosis of typhoid fever, those presenting with at least 3 days of fever, the efficacy estimate increased to 85.1% [ 20 ]. Similar vaccine efficacy was observed in Malawi, with an efficacy estimate of 80.7% (intention-to-treat population) and 83.7% (per protocol population) against blood culture-confirmed typhoid fever among children 9 months through 12 years of age, after 18 months of study follow-up ( Table 1 ) [ 21 ]. In a cluster-randomized trial in Dhaka, Bangladesh total effectiveness of TCV was 85% among vaccinated children aged 9 months to 15 years [ 22 ].…”
Section: Tyvac Clinical Trialssupporting
confidence: 56%
“…Similarly, a clusterrandomized study of over 60,000 children in Bangladesh found an overall vaccine protection of 57 percent (443). A Phase 3 study of over 28,000 children in Malawi compared TCV against meningococcus A vaccine and found an overall efficacy of 81 percent (444). Two Phase 2 studies in Burkina Faso confirmed the safety of TCV and its compatibility with other routine immunizations (445,446).…”
Section: Development Of Vaccines Against Salmonellamentioning
confidence: 93%